Mohammad Arkoun’s Theory of Qur’ānic Hermeneutics: A Critique - Solihu, Abdul Kabir Hussain (Intellectual Discourse, 2006)
Abstract: Mohammad Arkoun has been credited with the much needed attention to the Qur’ānic hermeneutics. A Textual analysis of his writings shows that his major concern is the methodology of interpretation and that he studied the Qur’ān for the sake of methodology. He questions the authenticity of the Qur’ān as well as its truth claim. His presentation reads more like mathematics than a textual analysis. Consequently, his methodological discussion has been largely neglected.